Lactic acid production from pretreated corn stover with recycled streams. (April 2020) - Chen, Hao; Su, Zihang; Wang, Yong; Wang, Boxuan; Si, Zhihao; Lu, Jie; Su, Changsheng; Ren, Wenqiang; Chen, Huidong; Cai, Di; Qin, Peiyong
Graphical abstract: Highlights: Fed-batch SSF-membrane integration process was performed for LA production. Cellulase was recycled by the integrated process and reused in following operations. Nutrients and wastewater discharge were significantly reduced in the process. LA yield of 0.389 g g −1 was obtained using the recycling the waste streams. Wastewater and cellulase cost were reduced by 73.7 % and 47.4 %. Abstract: In order to overcome bottlenecks of the high amount of cellulase consumption in lignocellulosic l -Lactic acid (LA) production, a non-sterilized fed-batch simultaneous saccharification and fermentation (SSF) -membrane separation integration process was established in this current work. During the process, residual cellulase that remaining in the waste aqueous solution and solid residuals of corn stover (CS) were recycled and reused in subsequent fermentations. A total 6 rounds of operation were performed. Averagely, LA yield of 0.389 g g −1 (pretreated CS) was achieved, which was 1.20 times higher than that of the conventional process without waste stream recycling. Moreover, the wastewater discharge and the cost of nutrients for fermentation can also hugely decrease. Results indicated that cellulase, wastewater discharge and nutrients consumption of the process reduced by 47.4 %, 73.7 % and 86.1 %, respectively. This study opens a promising way for the reduction of second-generation LA production cost, which could significantly change the economic feasibility of the LA biorefineries.